47th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference<BR&amp;gt; 14th AIAA/ASME/AHS Adap 2006
DOI: 10.2514/6.2006-1750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Damage Path Predictions for Composite Laminates by Explicit and Standard Finite Element Analysis Tools

Abstract: Splitting, ultimate failure load and the damage path in center notched composite specimens subjected to in-plane tension loading are predicted using progressive failure analysis methodology. A 2-D Hashin-Rotem failure criterion is used in determining intra-laminar fiber and matrix failures. This progressive failure methodology has been implemented in the Abaqus/Explicit and Abaqus/Standard finite element codes through user written subroutines "VUMAT" and "USDFLD" respectively. A 2-D finite element model is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 14 publications
9
44
0
Order By: Relevance
“…The use of an explicit analysis code for simulating the American Institute of Aeronautics and Astronautics progressive damage of statically loaded specimens is documented in the author's previous work [18] but has much to do with the desire to predict fast running cracks in the future. The progressive damage analysis methodology includes intralaminar and interlaminar damage initiation and progression.…”
Section: Progressive Damage Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The use of an explicit analysis code for simulating the American Institute of Aeronautics and Astronautics progressive damage of statically loaded specimens is documented in the author's previous work [18] but has much to do with the desire to predict fast running cracks in the future. The progressive damage analysis methodology includes intralaminar and interlaminar damage initiation and progression.…”
Section: Progressive Damage Analysismentioning
confidence: 99%
“…This led to a 12% over-prediction in failure load. In the authors' previous research [18] it was observed that a modeling approach that included only the intralaminar damage modes, underpredicted the failure load by 20% in an un-stiffened notched tension loaded laminate, where significant delamination was observed experimentally. These results support the inclusion of interlaminar effects in future code development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One criterion used in this investigation is the 2-D Hashin-Rotem (H-R) failure theory [2], which is also used in Ref. [5]. This lamina theory is the simplest, empirical theory that still retains the transversely isotropic nature of unidirectional ber composites.…”
Section: Failure Criteriamentioning
confidence: 99%
“…A micromechanics model, the Generalized Method of Cells (GMC) developed by Paley and Aboudi [3], is used to evaluate the 3-D Tsai-Hill failure criterion [4] in the matrix phase at the micro-level, and a maximum stress criterion is utilized for ber failure. Results from the two different nite element models are examined and compared with experimental data from Bogert et al [5] in Section .…”
Section: Introductionmentioning
confidence: 99%